ANALYSIS OF STUDENTS' ABILITY IN WRITING JOB APPLICATION LETTERS - Zega, Riswan; Zai, Asnini Junita; Waruwu, Mewi Dinda Arcila; Gulo, Ceria Putri Damai; Zendrato, Citra Kasih; Telaumbanua, Citra Wati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study analyzed the ability of 6th semester students of Class A of the English Education Study Program of the University of Nias in writing a job application letter. Using a qualitative descriptive approach, this study evaluated a population of 35 people and 12 samples using purposive sampling, analyzing student letters based on three main criteria: opening, body, and closing sections. Data collection techniques used written tests and inductive data analysis. The criteria used to analyze students' ability in writing application letters were from â€œExcellentâ€ to â€œPoorâ€. The results showed varying levels of proficiency in all three areas, with most students demonstrating â€œExcellentâ€ to â€œGoodâ€ proficiency. The main factors affecting students' performance included their understanding of letter format and structure, ability to articulate qualifications and experience, and use of professional language. The study concludes that while students generally demonstrated competence in writing job application letters, there is still room for improvement, especially in crafting more memorable letter openers and closers. These insights can inform teaching strategies to improve students' job application letter writing skills.